Examination of performance and hydration responses in elite triathletes during the Ironman World Championship Triathlon - Stearns, R. L.; Casa, D. J.; DeMartini, J. K.; Huggins, R. A.; Munoz, D.; Pagnotta, K. D.; Volk, B.; Maresh, C. M. (Journal of Athletic Training, 2012)
Context: Physiological demands for extreme endurance events, such as an Ironman triathlon, are very unique. Within the limited number of athletes participating in such events, even less is known regarding the elite level athletes that compete. Objective: Examine the hydration responses and performance characteristics of elite level triathletes during the Ironman World Championship race. Design: Observational field study. Setting: 2011 Ironman World Championships in Kona, Hawaii (28.9°C, 71% relative humidity). Patients or Other Participants: 33 subjects (n=22 males, 11 females) entered in the Ironman World Championships participated (Mean± SD: age= 40± 11y; height= 174.5± 9.1cm; weight =70±11.8kg; percent body fat= 11.4 ±4.1%). Interventions: No intervention occurred. Main Outcome Measures: Data collection occurred prior to (PRE), immediately post (POST), 24 hours (24h) and 48 hours (48h) following the race. A one-way repeated measures ANOVA with Bonferroni corrections were performed to examine differences across time for perceived thirst, perceived pain, urine specific gravity (Usg), urine color (Ucol), body mass loss (BML) and percent BML (%BML). Pearson`s bivariate correlations were used for comparisons with finishing time. Alpha level was set a priori at 0.05. Results: Average finish time (h:min) was 11:03±1:25h (males:10:34±1:08h, females: 12:00± 1:30h). Average sweat rate was 1.6±0.6L/h(males:1.7±0.6L/ h, females :1.±0.5L/h). Significant differences occurred for POST BML (-1.7±0.9kg) vs. 24h, and 48h BML (0.9±1.4, -0.1±1.2kg, respectively; p<0.001). No significant correlation occurred between BML and finishing time (r=0.216, p=0.242). %BML at POST was 2.3±1.6% and was not correlated with finishing time (r=0.124, p=0.505). Usg was significantly lower PRE (1.011±0.007) vs. POST (1.021± 0.007, p<0.001), 24h (1.024±0.008, p<0.001), and 48h (1.016±0.006, p=0.006). While 24h Usg was similar to POST (p=0.15), it was significantly different from 48h Usg (p=<0.001). Ucol was significantly lower PRE (3±2), vs. POST, 24h and 48h (6±2, 6±1, 5±2 respectively, p<0.001). Thirst was significantly lower PRE (4±2) vs. POST (5±2, p=0.002), but not 24h and 48h. Conclusions: Participants reached thresholds for dehydration post race as demonstrated by BML and urine indices; however BML returned to baeline by 24h and Usg reached euhydrated standards (Usg<1.020) by 48h. BML was not correlated with a reduction in finish time. Overall these results indicate that elite triathletes were able to greatly minimize the degree of dehydration during the race (2.3% BML post race), especially considering the duration of the event and high sweat rates (estimations of total fluid losses based on sweat rates range from 15.5L for women and 18L for men). Athletes also demonstrated an ability to return quickly to pre-race body mass.